Dual-pathway protection: physical activity buffers the relationship between perceived stress and problematic smartphone use via social anxiety by a moderated mediation model in Chinese college students - Liu, Ningning; Han, Xiaoyuan; Dai, Xinghong; Zhang, Guofeng (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the dual-pathway mechanism through which physical activity mitigates problematic smartphone use (PSU) among Chinese college students, examining the mediating role of social anxiety and the moderating effects of physical activity within a stress-PSU framework.MethodsGeneral stress theory was introduced to explore the intrinsic mechanisms by which perceived stress influences PSU. A total of 2,905 undergraduate students from universities in Shandong Province were selected using a convenient sampling method. Validated scales were used to measure perceived stress (PSS-14), social anxiety (IAS), physical activity (PARS-3) and PSU tendency (MPATS). Data analysis included correlation tests, regression analysis and moderated mediation modeling (PROCESS Macro Model 4/15).Results(1) There was a significant positive correlation between perceived stress, social anxiety and problematic smartphone use (All P < 0.01). Significant gender differences were found in social anxiety (P < 0.001) and problematic smartphone use (P < 0.05). (2) Path analysis revealed: A significant direct effect of perceived stress on PSU (β = 0.537, 95%CI[0.490, 0.586]), accounting for 70.94% of the total effect. Social anxiety mediated 29.06% of the effect (indirect effect = 0.220, 95%CI[0.195, 0.244]). (3) Physical activity demonstrated dual moderating effects: Buffered the direct stress-PSU pathway (β = −0.005, P < 0.001). Attenuated the social anxiety-PSU association (interaction β = 0.002, P < 0.05)ConclusionPhysical activity disrupts the stress-PSU cycle through two synergistic mechanisms: directly reducing stress-driven addiction and decoupling social anxiety from excessive smartphone use. Universities should implement structured physical activity programs as a dual-path intervention against PSU.